The advantages of UK Biobank's open‐access strategy for health research. (2nd August 2019) - Conroy, M.; Sellors, J.; Effingham, M.; Littlejohns, T. J.; Boultwood, C.; Gillions, L.; Sudlow, C. L. M.; Collins, R.; Allen, N. E.
Abstract: Ready access to health research studies is becoming more important as researchers, and their funders, seek to maximize the opportunities for scientific innovation and health improvements. Large‐scale population‐based prospective studies are particularly useful for multidisciplinary research into the causes, treatment and prevention of many different diseases. UK Biobank has been established as an open‐access resource for public health research, with the intention of making the data as widely available as possible in an equitable and transparent manner. Access to UK Biobank's unique breadth of phenotypic and genetic data has attracted researchers worldwide from across academia and industry. As a consequence, it has enabled scientists to perform world‐leading collaborative research. Moreover, open access to an already deeply characterized cohort has encouraged both public and private sector investment in further enhancements to make UK Biobank an unparalleled resource for public health research and an exemplar for the development of open‐access approaches for other studies. Abstract :